Virtual Services in the Health Sciences Library: A Handbook - Barbara M. Pope (Journal of the Medical Library Association, 2023)
Health sciences libraries serving universities and medical facilities have long used technology to provide library services, but COVID-19 presented libraries with unique challenges. Libraries shut their doors and adapted to conducting reference, instruction, and outreach, remotely. For some libraries described in Virtual Services in the Health Sciences Library: a Handbook, those services had been done in the library; for others, the library had considered adding virtual services. For those libraries that have not made the jump, this text presents strategies to which all health sciences libraries would find a useful reference. Given its practical strategies and engaging text, this reviewer finds Virtual Services in the Health Sciences Library: a Handbook to be an inspiring and a highly recommended reference for health sciences libraries.